Efforts of Social workers to help Alzheimer’s patient’s families in solving their problems Study applied to Social Workers who are working in governmental hospitals in Makkah, Jeddah and eastern region - Alfalah, Roqiah Mohammad (Journal of Humanities & Social Sciences, 2021)
This study aims to identify the efforts of social workers in helping the families of Alzheimer’s patients to face their social, economic and psychological problems. Also, to identify the obstacles that hinder social workers from achieving their goals in helping the families of Alzheimer’s patients face their problems, whether these obstacles are related to the medical institution, to the family of an Alzheimer’s patient, or related to the social workers themselves. In addition, to identify the necessary proposals to face these obstacles, and come up with a set of recommendations that can help social workers achieve their goals in helping families of Alzheimer’s patients to face their problems. his study is considered one of the descriptive studies that relied on the comprehensive social survey methodology for social workers that are working in government hospitals in Jeddah, Makkah and the Eastern Province and the number (67) specialists and medical social service workers. The researcher relied on the questionnaire tool for data collection. The study found several results, the most important of which are One of the most professional effort practiced by social workers is helping families of Alzheimer’s patients face their social problems is to activate the role of the patients’ families in the process of implementing the treatment plan, One of the most professional effort practiced by social workers to help families of Alzheimer’s patients to face their psychological problems is to enlighten the caregivers of an Alzheimer’s patient with the importance of the psychological help provided by the social worker to support their care capability for the patient, One of the most professional effort practiced by social workers to help families of Alzheimer’s patients face their economic difficulties is to explain to the families of Alzheimer’s patients how to obtain financial aid from government and private institutions and associations.